2004
DOI: 10.1093/oxfordjournals.schbul.a007091
|View full text |Cite
|
Sign up to set email alerts
|

Siblings of Patients With Schizophrenia: Sibling Bond, Coping Patterns, and Fear of Possible Schizophrenia Heredity

Abstract: Siblings of schizophrenia patients are from the patient's perspective important support providers, but most studies on family burden have focused on the parental role. This study aims to develop a detailed analysis of the psychological aspects of having a sibling with schizophrenia. We did a qualitative study with audiotaped semistructured interviews of 16 siblings. The reliability of the inductive categorization of data was high. A unifying theme appeared to be an emotional sibling bond characterized by feeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
1
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 38 publications
8
73
1
9
Order By: Relevance
“…Consistent with the literature on schizophrenia (Friedrich et al, 2008;Landeen et al, 1992), all of the siblings indicated that they required general information about AN and opportunities to discuss how to apply such information to their sibling and family. Similar to siblings of affected siblings with other mental illnesses (Lukens et al, 2004;Stalberg et al, 2004), the participants in this study strongly recommended that clinicians be non-blaming, empathic and supportive. Furthermore, siblings suggested that workshops or support groups specifically for siblings would be very helpful.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Consistent with the literature on schizophrenia (Friedrich et al, 2008;Landeen et al, 1992), all of the siblings indicated that they required general information about AN and opportunities to discuss how to apply such information to their sibling and family. Similar to siblings of affected siblings with other mental illnesses (Lukens et al, 2004;Stalberg et al, 2004), the participants in this study strongly recommended that clinicians be non-blaming, empathic and supportive. Furthermore, siblings suggested that workshops or support groups specifically for siblings would be very helpful.…”
Section: Discussionmentioning
confidence: 79%
“…Barak and Solomon (2005) found that the quality of the sibling relationship deteriorated over time and that non-affected siblings reported a more distant relationship with their parents and the affected sibling than normal controls with their own parents and siblings. Qualitative studies have revealed a full spectrum of emotional responses from siblings including sorrow and guilt over being healthy and that their sibling was suffering (Stalberg, Ekerwald, Dverre, & Hultman, 2004), and feelings of ambivalence towards their ill sibling (Lukens, Thorning, & Lohrer, 2004;Stalberg et al, 2004). Siblings also describe positive aspects of the caregiving experience including increased empathy and emotional responsiveness to others and greater family cohesion as a result of the illness (Greenberg, Greenley, & Benedict, 1994;Horwitz, 1994;Lukens et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28,29]), the relationships between siblings are unique in that they are longlasting. Anna's feelings of helplessness and frustration over not understanding her brother and not gaining understanding of him from the formal psychiatric caregivers seem to be overwhelming.…”
Section: Discussionmentioning
confidence: 99%
“…Für eine Ersterkrankung fällt eine ausgeprägte und andauernde Ne− gativsymptomatik auf, möglicherweise bestand schon vor der jetzigen psychotischen Episode ein längeres Prodromalstadium. [16,17]. Ängste von Geschwistern vor der eigenen Erkrankung sind aber auch realistisch in der Tatsache begründet, dass sich das Lebenszeitrisiko für eine Erkrankung aus dem schizophrenen Formenkreis von 1 % in der Allgemeinbevölkerung für Menschen mit einem schizophren erkrankten Geschwister auf ca.…”
Section: Diskussionunclassified